A novel cooperative clustering approach based on multi-criteria decision-making for IoV. (25th March 2022) - Bersali, Mahmoud; Rachedi, Abderrezak; Bouarfa, Hafida; Badjara, Mohamed El Amine
The introduction of the Internet of Things (IoT) has gradually transformed conventional vehicular ad-hoc networks (VANETs) into a new paradigm known as the internet of vehicles (IoV), which has lately been the focus of several researchers. Frequent topological changes and the scalability issue are major problems that affect the performance of IoV. In order to overcome the previous challenges, we propose in this paper a novel cooperative clustering approach based on multi-criteria decision-making (MCDM) methods for IoV named: CMC-IoV, which combines both analytic hierarchy process (AHP) and preference ranking organisation method for enrichment evaluation (PROMETHEE) methods to select the most appropriate leader for each cluster. CMC-IoV supports the cluster stability by selecting a vice cluster leader (VCL) as a complement to the Cluster Leader. We validate the efficiency of the proposed approach by using a realistic scenario from Highway 640 in Knoxville, USA as an input to the NS-3 network simulator.